ANALISIS ANCAMAN KEBERADAAN KELOMPOK KHILAFATUL MUSLIMIN SEBAGAI ORGANISASI RADIKAL DI INDONESIA - Al Hadid Dwi Putera Ma'ruf (Kajian Ilmu Kepolisian dan Anti Korupsi Universitas Bhayangkara Jakarta Raya, 2025)
Khilafatul Muslimin (KM) is an organization established with the aim of creating a caliphate, a system of governance based on exclusive Islamic leadership principles. This group promotes a caliphate ideology that contradicts Pancasila, seeking to establish a government based on Islamic law and singular Islamic leadership, rejecting Indonesia’s principles of pluralism and democracy. The impact of KM’s ongoing efforts to establish a caliphate poses a potential threat to Indonesia’s sovereignty. This research is conducted to provide a threat analysis to address KM's presence in society. The research method used is a descriptive qualitative approach based on an inductive perspective. The results of the analysis, referring to Hank Prunckun's threat analysis framework, indicate that the threat level of KM’s existence is medium. Furthermore, advanced threat analysis shows that KM meets the threat factors as outlined by Kevin Riehle, namely intent, capability, and opportunity. This threat analysis from both approaches is further supported by explanations from Randy Borum’s Terrorist Mindset perspective.